Osmodehydrofreezing: An Integrated Process for Food Preservation during Frozen Storage - Maria C. Giannakourou; Efimia K. Dermesonlouoglou; Petros S. Taoukis (Foods, 2020)
Osmodehydrofreezing (ODF), a combined preservation process where osmotic dehydration is applied prior to freezing, achieves several advantages, especially in plant tissues, sensitive to freezing. OD pre-treatment can lead to the selective impregnation of solutes with special characteristics that reduce the freezing time and improve the quality and stability of frozen foods. ODF research has extensively focused on the effect of the osmotic process conditions (e.g., temperature, duration/composition/concentration of the hypertonic solution) on the properties of the osmodehydrofrozen tissue. A number of complimentary treatments (e.g., vacuum/pulsed vacuum, pulsed electric fields, high pressure, ultrasound) that accelerate mass transfer phenomena have been also investigated. Less research has been reported with regards the benefits of ODF during the subsequent storage of products, in comparison with their conventionally frozen counterparts. It is important to critically review, via a holistic approach, all parameters involved during the first (osmotic dehydration), second (freezing process), and third stage (storage at subfreezing temperatures) when assessing the advantages of the ODF integrated process. Mathematical modeling of the improved food quality and stability of ODF products during storage in the cold chain, as a function of the main process variables, is presented as a quantitative tool for optimal ODF process design.